2018
DOI: 10.1016/j.scitotenv.2017.11.302
|View full text |Cite
|
Sign up to set email alerts
|

Fe3+-saturated montmorillonite effectively deactivates bacteria in wastewater

Abstract: • Fe 3+ -saturated montmorillonite's antibacterial activity was studied.• Wastewater bacteria was deactivated effectively by Fe 3+ -saturated montmorillonite.• Fe 3+ -saturated montmorillonite deactivated bacteria possibly by cell membrane damage.• Fe 3+ -saturated montmorillonite can disinfect bacteria-contaminated water. G R A P H I C A L A B S T R A C TThe graphic abstract figure is only for simple demonstration of possible reaction processes. Sizes of different components do not reflect their actual relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 55 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…As it turned out, some of the data presented in the literature indicated the antibacterial effect of iron-containing samples [11,21]. For example, in the study by Qin C., et al, the antibacterial activity of montmorillonite saturated with Fe 3+ was investigated using urban wastewater.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it turned out, some of the data presented in the literature indicated the antibacterial effect of iron-containing samples [11,21]. For example, in the study by Qin C., et al, the antibacterial activity of montmorillonite saturated with Fe 3+ was investigated using urban wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial decontamination efficiency (loss of bacterial viability) was 92±0.64% when the secondary wastewater was mixed with Fe 3+ -saturated montmorillonite for 30 minutes and then increased to 97±0.61% after 4 hours. Nearly all (99.9%) E. coli and enterococci in the secondary wastewater were deactivated when the water was exposed to Fe 3+ -saturated montmorillonite for 1 hour [11]. One of possible action mechanisms is the suppression of microbial growth by trivalent iron via the formation of hydroxyl free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has several biological efficacies, such as antibacterial effects, anti-viral effects, and detoxification [27]. Qin et al reported that Fe 3+ -saturated montmorillonite could suppress bacterial activity in municipal wastewater effluents [28]. Germanium biotite has been used as a dietary material for preventing porcine reproductive and respiratory syndrome viruses [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these materials are nanomaterials with increased specific surface areas, allowing greater exposure of active sites. NNMs contain antibacterial atoms such as Fe and Cu due to their homogeneous substitution in the environment . In addition, their nanomorphology results in a significant specific surface area, making them effective agents against bacteria both independently and as carriers.…”
Section: Biomedical Applications Of Composites Based On Nnmsmentioning
confidence: 99%